Preverbal infants expect agents exhibiting counterintuitive capacities to gain access to contested resources - Meng, X; Nakawake, Y; Burdett, E; Jong, J; Whitehouse, H (Springer Nature, 2021)
Claims to supernatural power have been used as a basis for authority in a wide range of societies, but little is known about developmental origins of the link between supernatural power and worldly authority. Here, we show that 12- to 16-month-old infants expect agents exhibiting counterintuitive capacities to win out in a two-way standoff over a contested resource. Infants watched two agents gain a reward using either physically intuitive or physically counterintuitive methods, the latter involving simple forms of levitation or teleportation. Infants looked longer, indicating surprise, when the physically intuitive agent subsequently outcompeted a physically counterintuitive agent in securing a reward. Control experiments indicated that infants’ expectations were not simply motived by the efficiency of agents in pursuing their goals, but specifically the deployment of counterintuitive capacities. This suggests that the link between supernatural power and worldly authority has early origins in development.